The effect of baking and enzymatic treatment on the structural properties of wheat starch. (15th December 2016) - Fuentes, Catalina; Zielke, Claudia; Prakash, Manish; Kumar, Puneeth; Peñarrieta, J. Mauricio; Eliasson, Ann-Charlotte; Nilsson, Lars
Highlights: Starch is extracted from bread crumb for analysis of physico-chemical properties. Changes in starch properties occur as effect of breadmaking. Baking and addition of α-amylase increase the average degree of branching. Abstract: In this study, bread was baked with and without the addition of α-amylase. Starch was extracted from the baked bread and its molecular properties were characterized using 1 H NMR and asymmetric flow field-flow fractionation (AF4) connected to multi-angle light scattering (MALS) and other detectors. The approach allows determination of molar mass, root- mean-square radius and apparent density as well as the average degree of branching of amylopectin. The results show that starch size and structure is affected as a result of the baking process. The effect is larger when α-amylase is added. The changes include both a decrease molar mass and size as well as an increase in apparent density. Moreover, an increase in average degree of branching and the number of reducing ends H-1(β-r) and H-1(α-r) can be observed.